Preferred orientation single crystal lithium-rich manganese-based positive electrode material, preparation method thereof and lithium ion battery

By adjusting the synthesis process and sintering conditions in the lithium-rich manganese-based positive electrode material, it is optimized to grow along the (003) crystal plane, the problem of insufficient stability and rate performance of the material under high-rate charging and discharge conditions is solved, and a lithium-ion battery positive electrode material with high energy density and long life is achieved.

CN119786590AActive Publication Date: 2025-04-08CHINA AUTOMOTIVE BATTERY RES INST CO LTD

Patent Information

Application Number
CN202510272728.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-08
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

In practical applications, lithium-rich manganese-based cathode materials have problems such as low efficiency, serious capacity attenuation, and poor rate performance, which limits their promotion in lithium-ion batteries.

Method used

By controlling the synthesis process, lithium-rich manganese-based materials are grown along the (003) crystal surface, and composite molten salt sintering technology is used to control the sintering temperature and time to achieve efficient optimal crystal surface growth of the material.

Benefits of technology

It significantly improves the electrochemical performance of the material, especially the stability under high-rate charging and discharge conditions, extends the battery life and increases the energy density of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786590A_ABST
    Figure CN119786590A_ABST
Patent Text Reader

Abstract

The invention provides a preferred orientation single crystal lithium-rich manganese-based positive electrode material, a preparation method thereof and a lithium ion battery, and relates to the technical field of battery positive electrode material preparation. The lithium-rich manganese-based positive electrode material is in a single crystal morphology, and in a diffraction pattern obtained by adopting an XRD (X-Ray Diffraction) instrument taking Cu K alpha as an incident light source, the peak intensity ratio I (003) / I (104) gt of a (003) peak of which 2 theta is positioned at 18.6 + / -0.1 degrees to a (104) peak of which 2 theta is positioned at 44 + / -0.5 degrees; 2. The single crystal lithium-rich manganese-based material with the specific crystal face preferentially growing is prepared, the material preferentially grows along the (003) crystal face by regulating and controlling the synthesis process of the material, the electrochemical performance of the material can be remarkably improved, and especially the stability under the high-rate charging and discharging condition can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery positive electrode material preparation, and in particular to a preferentially oriented single crystal lithium-rich manganese-based positive electrode material and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] With the continuous growth of global energy demand and the increasing attention to environmental protection, lithium-ion batteries, as an efficient and environmentally friendly energy storage device, have received widespread attention and application. Li-rich Mn-based cathode materials have gradually become a research hotspot due to their high capacity (theoretical capacity exceeds 250 mAh / g), low cost and good thermal stability. This type of material can significantly improve the energy density of the battery through the transition state reaction of lithium ions and is suitable for the next generation of high energy density lithium-ion batteries. However, there are still some problems with lithium-rich manganese-based materials, such as low first coulombic efficiency, severe capacity decay, and poor rate performance, which limit their promotion in practical applications.

[0003] In order to solve these problems, in recent years, scientists have proposed to improve the electrochemical properties of lithium-rich manganese-based materials by means of structural design, doping modification, nano-sizing and single crystallization. Among them, the research on single crystalization has attracted widespread attention. Compared with polycrystalline materials, single crystal materials have better structural stability and electrochemical properties because they do not have grain boundaries, thereby reducing the structural collapse and side reactions of the materials during the charging and discharging process. For example, Chinese patent CN107834063B uses potassium chloride as an additive to obtain a single-crystalline one-dimensional lithium-rich material, and Chinese patent CN109537054A uses peracetic acid as an auxiliary agent to obtain a single-crystalline lithium-rich manganese-based positive electrode material. In addition, the single crystal structure shows better stability under high-rate cycling and can effectively reduce capacity attenuation. However, conventional single crystal synthesis methods can only utilize the structural advantages of single crystals, and cannot give full play to the advantages of advantageous crystal faces. By selectively designing the crystal face, the structural stress of the material during the charging and discharging process is reduced, further improving the cycle stability and long life.

[0004] Preferential growth of crystal faces refers to the process of controlling the crystal growth conditions during the synthesis of materials so that certain crystal faces are preferentially exposed during the growth of materials, thereby improving the physical and chemical properties of materials. Different crystal faces have a significant impact on the electrochemical behaviors of materials such as ion migration, electron conduction and surface reaction. For positive electrode materials of lithium-ion batteries, preferential growth of crystal faces can effectively improve the diffusion path of lithium ions in the materials, reduce the charge transfer resistance, and thus improve the rate performance and cycle stability of the materials. In lithium-rich manganese-based positive electrode materials, studies have found that the (003) crystal face has a significant effect on the electrochemical properties of the materials. Materials with exposed (003) crystal faces show higher electronic conductivity, faster lithium ion migration rate and better cycle stability. Therefore, it is necessary to develop a preparation method for single-crystal lithium-rich manganese-based materials that can achieve preferential growth of the (003) crystal face, which can combine the structural advantages of single-crystal materials and the electrochemical performance advantages of preferential growth of the (003) crystal face, so as to obtain high-energy-density and long-life lithium-ion battery positive electrode materials. Summary of the invention

[0005] The present invention prepares a single-crystal lithium-rich manganese-based material with preferential growth of a specific crystal plane. By regulating the synthesis process of the material, it is made to preferentially grow along the (003) crystal plane, which can significantly improve the electrochemical performance of the material, especially the stability under high-rate charge and discharge conditions.

[0006] One of the purposes of the present invention is to provide a single-crystal lithium-rich manganese-based positive electrode material with preferential orientation.

[0007] The second object of the present invention is to provide a method for preparing the preferentially oriented single crystal lithium-rich manganese-based positive electrode material.

[0008] The third object of the present invention is to provide a lithium-ion battery, including the preferentially oriented single-crystal lithium-rich manganese-based positive electrode material.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In a first aspect, the present invention provides a single crystal lithium-rich manganese-based positive electrode material with a preferred orientation, wherein the chemical formula of the lithium-rich manganese-based positive electrode material is Li[Li x M (1-x) ]O2, wherein M is at least one of Mn, Ni or Co, 0 <x<1; The lithium-rich manganese-based positive electrode material is Cu Kα In the diffraction pattern obtained by the XRD instrument with the incident light source, the peak intensity ratio of the (003) peak with 2θ located at 18.6±0.1° to the (104) peak with 2θ located at 44±0.5° is I(003) / I(104)>2, preferably I(003) / I(104)≥3; The lithium-rich manganese-based positive electrode material has a single crystal morphology and a layered structure of R-3m space group α-NaFeO2.

[0010] Preferably, the median particle size D50 of the single crystal lithium-rich manganese-based positive electrode material is 0.1 μm-10 μm, and the single crystal morphology is at least one of a cube, a cuboid, a hexahedron, a tetrahedron, and an octahedron.

[0011] Its (003) crystal plane proportion is significantly higher than that of conventional single crystal lithium-rich manganese-based materials.

[0012] The peak intensity ratio (I(003) / I(104)) is used to measure the degree of orientation of the (003) crystal plane in the material. The higher the peak intensity ratio, the stronger the preferred orientation of the (003) crystal plane relative to the (104) crystal plane, that is, during the crystal growth process, more (003) crystal planes are exposed on the surface of the material. This highly oriented (003) crystal plane can increase the migration rate and electronic conductivity of lithium ions in the material, thereby improving the electrochemical performance and cycle stability of the battery. Therefore, a high peak intensity ratio reflects that the material has better electrochemical performance in structure.

[0013] In a second aspect, the present invention provides a method for preparing a preferentially oriented single-crystal lithium-rich manganese-based positive electrode material, comprising the following steps: (1) Mixing an aqueous solution A containing a metal salt and an aqueous solution B containing a precipitant and a complexing agent, performing a coprecipitation reaction at 45-75° C., controlling the pH value to be 10-13, washing, filtering, and drying the reaction product to obtain a cathode material precursor; (2) The cathode material precursor obtained in step (1) is mixed evenly with a sodium source and a lithium source, and sintered to obtain a single crystal precursor P. The chemical formula of the single crystal precursor P is (Na x Li y M z )O2, wherein M is at least one of Mn, Ni or Co, 0.6≤x≤0.9, preferably 0.8≤x≤0.9, 0 <y≤0.3,0.7≤z<1,y+z=1; (3) The single crystal precursor P is fully mixed with the molten salt and then sintered. The sintered product is washed, filtered, and dried to obtain the final product Li[Li x M (1-x) ]O2 (M is at least one of Mn, Ni or Co, 0 <x<1)。

[0014] In some embodiments, the metal salt in step (1) is at least one of sulfate, nitrate, oxalate or acetate, and the concentration of metal ions in aqueous solution A is 0.2-2 mol / L; the precipitant includes sodium hydroxide and / or potassium hydroxide, and the concentration of hydroxide ions in aqueous solution B is 1-3 mol / L; the complexing agent is ammonia water, and the concentration of ammonia water in aqueous solution B is 0.5-2 mol / L. For example, the metal salts are prepared according to the chemical formula to prepare soluble nickel salts, soluble manganese salts and soluble cobalt salts in corresponding proportions. The soluble nickel salts include any one or a combination of at least two of nickel sulfate, nickel acetate, nickel oxalate or nickel nitrate, the soluble manganese salts include any one or a combination of at least two of manganese sulfate, manganese acetate, manganese oxalate or manganese nitrate, and the soluble cobalt salts include any one or a combination of at least two of cobalt sulfate, cobalt acetate, cobalt oxalate or cobalt nitrate.

[0015] In some embodiments, the lithium source in step (2) is any one of lithium acetate, lithium nitrate, lithium carbonate, lithium oxalate, and lithium hydroxide, or a combination of at least two thereof; and the sodium source is any one of sodium oxide, sodium hydroxide, sodium carbonate, sodium nitrate, and sodium oxalate, or a combination of at least two thereof.

[0016] In some embodiments, the sintering in step (2) includes: a primary sintering and a secondary sintering performed sequentially, wherein the primary sintering is performed at a temperature of 400 to 700° C. for 3 to 6 hours, and the secondary sintering is performed at a temperature of 800 to 1100° C. for 10 to 30 hours.

[0017] In some embodiments, the molten salt in step (3) includes one or more of lithium chloride, lithium nitrate, and lithium hydroxide; the molar ratio of lithium ions in the molten salt to sodium ions in the single crystal precursor P is greater than 3. The lithium ions in the molten salt are ion-exchanged with the sodium ions in the single crystal precursor P, and the sodium is subsequently washed away.

[0018] In some embodiments, the sintering temperature in step (3) is 330° C.-600° C., and the sintering time is 1-20 hours. The lithium salt can form a molten salt at the sintering temperature.

[0019] In a third aspect, the present invention provides a lithium-ion battery comprising the above-mentioned preferentially oriented single-crystal lithium-rich manganese-based positive electrode material.

[0020] Beneficial effects: The inventor unexpectedly discovered that by precisely controlling the sintering conditions and the composition and sintering conditions (temperature) of the composite molten salt, the (003) crystal plane of the lithium-rich manganese-based positive electrode material can be preferentially grown, thereby significantly improving its electrochemical performance. Specifically, the sintering process includes primary sintering (temperature 400-700°C, time 3-6 hours) and secondary sintering (temperature 800-1100°C, time 10-30 hours), as well as composite molten salt sintering (temperature 330°C-600°C, time 1-20 hours). These sintering conditions provide a suitable thermodynamic environment for the growth of crystals, and the liquid phase environment formed by the composite molten salt during the sintering process promotes the rapid growth of crystals and the directional arrangement of crystal planes. The control of sintering temperature and time provides appropriate thermodynamic conditions for the growth of crystals, while the liquid phase environment of the composite molten salt provides a rapid mass transfer and nucleation process. This synergistic effect can significantly increase the growth rate of crystals and the degree of directional arrangement of crystal planes. By adjusting the composition ratio of the molten salt, the preferential growth effect of the crystal plane can be further optimized. This synergistic regulation mechanism not only improves the structural stability of the material, but also significantly enhances the migration rate and electronic conductivity of lithium ions, providing a new technical path for the preparation of high-performance lithium-ion battery positive electrode materials.

[0021] The present invention prepares a single-crystal lithium-rich manganese-based material with preferential growth of a specific crystal plane, so that it preferentially grows along the (003) crystal plane, which can significantly improve the electrochemical performance of the material, especially the stability under high-rate charge and discharge conditions.

[0022] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the XRD pattern of Example 1; Figure 2 is the SEM image of Example 1; Figure 3 is the XRD pattern of Example 2; Figure 4 is the SEM image of Example 2; Figure 5 is the XRD pattern of Example 3; Figure 6 is the SEM image of Example 3; Figure 7 is the XRD pattern of Example 4; Figure 8 is the SEM image of Example 4; Fig. 9 is the XRD pattern of Comparative Example 1; Fig.10 It is the SEM picture of comparative example 1; Fig.11 is the XRD pattern of Comparative Example 2; Fig.12 It is the SEM picture of comparative example 2; Fig.13 is the XRD pattern of Comparative Example 3; Fig.14 This is the SEM image of Comparative Example 3. DETAILED DESCRIPTION

[0024] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0025] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0026] XRD test: The material phase structure is determined by X-ray powder diffractometer (XRD), the manufacturer is Smart Lab 9 KW. The type of slide used is XRD special glass. Sample preparation: Each test is to fill the groove of the slide with the sample for testing. The scanning range of the test is 10-90°, the test rate is 10° / min, and the step size used is 0.02.

[0027] Specific surface area: The specific surface area was measured on a surface area analyzer from Guokangta Instrument Co., Ltd., the instrument model is QUADRASORB SI. The sample weight used is 3-5g.

[0028] Compaction density: The compaction density is tested using the UTM7305 battery powder compaction density tester. The test conditions include weighing a 2.0000g sample, using a φ13mm mold, compressing within the maximum test force of 300kN, holding the pressure for 10 seconds, and obtaining the compaction density data by precisely controlling the pressure and time.

[0029] Example 1 (1) According to the molar ratio of Mn:Ni:Co of 0.68:0.16:0.16, weigh the corresponding mass of manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate, dissolve them in water, and prepare a metal salt solution A with a concentration of 2 mol / L. At the same time, weigh sodium hydroxide and dissolve it in water to prepare a solution with a concentration of 2 mol / L, and add ammonia water with a concentration of 1 mol / L as a complexing agent, stir evenly, and obtain solution B. Under the condition of stirring speed of 330 rpm, solution A and solution B are slowly added dropwise to a certain amount of deionized water. The drop rate of solution A is controlled to 0.4 L / h, and the drop rate of solution B is adjusted to maintain the pH value of the system at 12. The coprecipitation reaction is carried out at 50°C for 18 hours. After the reaction is completed, the product is washed, filtered and dried to finally obtain the positive electrode material precursor Mn 0.68 Ni 0.16 Co 0.16 (OH)2.

[0030] (2) The cathode material precursor obtained in step (1) was mixed with lithium carbonate and sodium carbonate in a molar ratio of 0.9:0.05:0.33, and then placed in a muffle furnace and heated to 550°C at a heating rate of 5°C / min and kept at this temperature for 4 hours, and then heated to 850°C at a heating rate of 5°C / min, sintered for 20 hours, and cooled to room temperature to obtain the precursor P-Na 0.66 Li 0.1 (Mn 0.68 Ni 0.16 Co 0.16 ) 0.9 O2.

[0031] (3) Precursor P and composite molten salt (lithium hydroxide: lithium chloride mass ratio = 37:63), with the molar ratio of lithium ions in the molten salt to sodium ions in the single crystal precursor P being 10:1, are fully mixed and placed in a crucible, sintered at 400°C for 4h, cooled to room temperature, washed, filtered, and dried.

[0032] The product was analyzed by XRD and had a crystal structure of α-NaFeO2 with R-3m space group and O3 phase. Figure 1 , characterized by a ratio of (003) peak intensity to (104) peak intensity of 3.89. The peak intensity ratio (I(003) / I(104)) is used to measure the degree of orientation of the (003) crystal plane in the material. The higher the peak intensity ratio, the more (003) crystal planes are exposed on the surface of the material. The SEM image of the product is shown in Figure 2 , which is characterized by single-crystalline particles with a size of approximately 2-5μm.

[0033] The prepared lithium-rich manganese-based positive electrode material with an oriented growth structure, acetylene black, polyvinylidene fluoride and N-methylpyrrolidone are mixed to form a slurry, which is evenly coated on the surface of an aluminum foil to obtain a positive electrode plate; then, a lithium plate is used as a negative electrode plate, and a 1 mol / L lithium hexafluorophosphate ethylene carbonate (EC) and dimethyl carbonate (DMC) solution (the volume ratio of EC to DMC is 1:1) is used as an electrolyte, and the batteries are assembled in a glove box to obtain a lithium-ion battery.

[0034] The assembled lithium-ion battery was tested for first-week charge and discharge performance and cycle performance using an electrochemical tester at a temperature of 25°C and a current density of 0.1C (1C = 200 mAg -1 ), the battery's initial charge and discharge performance was tested under the condition of charge and discharge voltage range of 2-4.8V. After activation for one week at 2.0-4.8V and 0.1C current density, the battery's cycle performance was tested at 1C charge and discharge current density and 2.0-4.8V voltage range. Its initial discharge specific capacity was 266.8mAh / g, and the 200-week capacity retention rate was 95.5%. The results are shown in Table 1.

[0035] Example 2 (1) The cathode material precursor obtained in step (1) of Example 1 was mixed with lithium carbonate and sodium carbonate in a molar ratio of 0.9:0.05:0.43, and then placed in a muffle furnace and heated to 550°C at a heating rate of 10°C / min and kept at this temperature for 4 hours, and then heated to 850°C at a heating rate of 10°C / min, sintered for 20 hours, and cooled to room temperature to obtain the precursor P-Na 0.86 Li 0.1 (Mn 0.68 Ni 0.16 Co 0.16 ) 0.9 O2.

[0036] (2) The precursor P and the composite molten salt (lithium hydroxide: lithium chloride = 37:63) were fully mixed and placed in a crucible. The mixture was sintered at 400 °C for 4 h. After cooling to room temperature, the mixture was washed, filtered and dried.

[0037] The product was analyzed by XRD and showed an O3 phase. Figure 3 , which is characterized by a ratio of (003) peak intensity to (104) peak intensity of 4.21. The SEM image of the product is shown in Figure 4 , which is characterized by single-crystalline particles with a size of approximately 2-5μm.

[0038] The electrochemical performance test method is the same as that of Example 1. The results are shown in Table 1. The initial discharge specific capacity is 275.3 mAh / g, and the 200-cycle capacity retention rate is 92.5%.

[0039] Example 3 (1) The cathode material precursor obtained in step (1) of Example 1 was mixed with lithium carbonate and sodium carbonate in a molar ratio of 0.9:0.05:0.43, and then placed in a muffle furnace and heated to 550°C at a heating rate of 10°C / min and kept at this temperature for 4 hours, and then heated to 850°C at a heating rate of 10°C / min, sintered for 20 hours, and cooled to room temperature to obtain the precursor P-Na 0.86 Li 0.1 (Mn 0.68 Ni 0.16 Co 0.16 ) 0.9 O2.

[0040] (2) The precursor P and the composite molten salt (lithium carbonate: lithium hydroxide = 74:26) were fully mixed and placed in a crucible. The mixture was sintered at 600 °C for 4 h. After cooling to room temperature, the mixture was washed, filtered and dried.

[0041] The product was analyzed by XRD and showed an O3 phase. Figure 5 , which is characterized by a ratio of (003) peak intensity to (104) peak intensity of 2.61. The SEM image of the product is shown in Figure 6 , which is characterized by single-crystalline particles with a size of approximately 2-5μm.

[0042] The electrochemical performance test method is the same as that of Example 1. The results are shown in Table 1. The initial discharge specific capacity is 259.4 mAh / g, and the 200-cycle capacity retention rate is 88.9%.

[0043] Example 4 (1) According to the molar ratio of Mn:Ni:Co of 0.65:0.3:0.05, weigh the corresponding mass of manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate, dissolve them in water, and prepare a metal salt solution A with a concentration of 2 mol / L. At the same time, weigh sodium hydroxide and dissolve it in water to prepare a solution with a concentration of 2 mol / L, and add ammonia water with a concentration of 1 mol / L as a complexing agent, stir evenly, and obtain solution B. Under the condition of stirring speed of 330 rpm, solution A and solution B are slowly added dropwise to a certain amount of deionized water. The drop rate of solution A is controlled to 0.4 L / h, and the drop rate of solution B is adjusted to maintain the pH value of the system at 12. The coprecipitation reaction is carried out at 50°C for 18 hours. After the reaction is completed, the product is washed, filtered and dried to finally obtain the positive electrode material precursor Mn 0.65 Ni 0.3 Co 0.05 (OH)2.

[0044] (2) The cathode material precursor obtained in step (1) was mixed with lithium carbonate and sodium carbonate in a molar ratio of 0.9:0.05:0.33, and then placed in a muffle furnace and heated to 550°C at a heating rate of 5°C / min and kept at this temperature for 4 hours, and then heated to 850°C at a heating rate of 5°C / min, sintered for 20 hours, and cooled to room temperature to obtain the precursor P-Na 0.66 Li 0.1 (Mn 0.65 Ni 0.3 Co 0.05 ) 0.9 O2.

[0045] (3) The precursor P and the composite molten salt (lithium hydroxide: lithium chloride = 37:63) were fully mixed and placed in a crucible. The mixture was sintered at 400 °C for 4 h. After cooling to room temperature, the mixture was washed, filtered and dried.

[0046] The product was analyzed by XRD and showed an O3 phase. Figure 7 , which is characterized by a ratio of (003) peak intensity to (104) peak intensity of 2.98. The SEM image of the product is shown in Figure 8 , which is characterized by single-crystalline particles with a size of approximately 2-5μm.

[0047] The electrochemical performance test method is the same as that of Example 1. The results are shown in Table 1. The initial discharge specific capacity is 263.9 mAh / g, and the 200-cycle capacity retention rate is 93.7%.

[0048] Comparative Example 1 The precursor obtained in step (1) of Example 1 was mixed evenly with lithium carbonate in a molar ratio of 1:1.15, and then placed in a muffle furnace and heated to 550°C at a heating rate of 10°C / min and kept warm for 4 hours, and then continued to heat to 850°C at a heating rate of 10°C / min, sintered for 15 hours, and cooled to room temperature in the furnace to obtain a conventional spherical lithium-rich manganese-based positive electrode material.

[0049] The product was analyzed by XRD and showed an O3 phase. Fig. 9 , which is characterized by the peak intensity ratio of (003) peak intensity to (104) peak intensity being far less than 2, only 1.2. The SEM image of the product is shown in Fig.10 , which is characterized by polycrystalline particles (secondary particles) with a size of about 5μm.

[0050] The electrochemical performance test method is the same as that of Example 1. The results are shown in Table 1. The initial discharge specific capacity is 262.5 mAh / g, and the 200-cycle capacity retention rate is 87.6%.

[0051] Comparative Example 2 The precursor obtained in step (1) of Example 1, lithium carbonate and potassium chloride are mixed uniformly in a molar ratio of 1:1.15:4, and then placed in a muffle furnace and heated to 550°C at a heating rate of 10°C / min and kept warm for 4 hours, and then continued to heat to 950°C at a heating rate of 10°C / min, sintered for 20 hours, and cooled to room temperature with the furnace. The product is washed, filtered and dried to obtain a conventional single crystal morphology of a lithium-rich manganese-based positive electrode material.

[0052] The product was analyzed by XRD and showed an O3 phase. Fig.11 , which is characterized by a ratio of (003) peak intensity to (104) peak intensity of 1.56. The SEM image of the product is shown in Fig.12 , which is characterized by single crystal particles with a size of about 5μm.

[0053] The electrochemical performance test method is the same as that of Example 1. The results are shown in Table 1. The initial discharge specific capacity is 250.9 mAh / g, and the 200-cycle capacity retention rate is 85.6%.

[0054] Comparative Example 3 (1) The positive electrode material precursor obtained in step (1) of Example 1 was mixed evenly with lithium carbonate and sodium carbonate in a molar ratio of 1:0.1:0.43, and then placed in a muffle furnace and heated to 550°C at a heating rate of 10°C / min and kept at this temperature for 4 hours, and then continued to heat to 850°C at a heating rate of 10°C / min, sintered for 20 hours, and cooled to room temperature in the furnace to obtain the precursor P.

[0055] (2) The precursor P and the composite molten salt (lithium hydroxide: lithium carbonate = 76:24) were fully mixed and placed in a crucible. The mixture was sintered at 700 °C for 4 h. After cooling to room temperature, the mixture was washed, filtered and dried.

[0056] The product was analyzed by XRD. Fig.13 , with O3 phase, the ratio of (003) peak intensity to (104) peak intensity is 1.45. The SEM image of the product is shown in Fig.14 , which is characterized by single crystal particles with a size of about 1-3μm.

[0057] The electrochemical performance test method is the same as that of Example 1. The results are shown in Table 1. The initial discharge specific capacity is 187.7 mAh / g, and the 200-cycle capacity retention rate is 64.5%.

[0058] Table 1

[0059] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. A preferentially oriented single crystal lithium-rich manganese-based positive electrode material, characterized in that: The lithium-rich manganese-based positive electrode material is Cu Kα In the diffraction pattern obtained by the XRD instrument with the incident light source, the peak intensity ratio of the (003) peak with 2θ located at 18.6±0.1° and the (104) peak with 2θ located at 44±0.5° is I(003) / I(104)>2; The lithium-rich manganese-based positive electrode material has a single crystal morphology and a layered structure of R-3m space group α-NaFeO2.

2. The preferentially oriented single crystal lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The median particle size D50 of the single crystal lithium-rich manganese-based positive electrode material is 0.1 μm-10 μm, and the single crystal morphology is at least one of a cube, a cuboid, a hexahedron, a tetrahedron, and an octahedron.

3. A method for preparing a preferentially oriented single crystal lithium-rich manganese-based positive electrode material according to claim 1 or 2, characterized in that: The following steps are involved: (1) Mixing an aqueous solution A containing a metal salt and an aqueous solution B containing a precipitant and a complexing agent, performing a coprecipitation reaction at 45-75° C., controlling the pH value to be 10-13, washing, filtering, and drying the reaction product to obtain a cathode material precursor; (2) The cathode material precursor obtained in step (1) is mixed evenly with a sodium source and a lithium source, and sintered to obtain a single crystal precursor P. The chemical formula of the single crystal precursor P is (Na x Li y M z )O2, wherein M is at least one of Mn, Ni or Co, 0.6≤x≤0.9, 0 <y≤0.3,0.7≤z<1,y+z=1; (3) The single crystal precursor P is fully mixed with the molten salt and then sintered. The sintered product is washed, filtered, and dried to obtain the final product.

4. The preparation method according to claim 3, characterized in that: The metal salt in step (1) is at least one of sulfate, nitrate, oxalate or acetate, and the concentration of metal ions in aqueous solution A is 0.2-2 mol / L.

5. The preparation method according to claim 3, characterized in that: The precipitant in step (1) includes sodium hydroxide and / or potassium hydroxide, and the concentration of hydroxide ions in aqueous solution B is 1 to 3 mol / L; the complexing agent is ammonia water, and the concentration of ammonia water in aqueous solution B is 0.5 to 2 mol / L.

6. The preparation method according to claim 3, characterized in that: The lithium source in step (2) is any one of lithium acetate, lithium nitrate, lithium carbonate, lithium oxalate, and lithium hydroxide, or a combination of at least two thereof; the sodium source is any one of sodium oxide, sodium hydroxide, sodium carbonate, sodium nitrate, and sodium oxalate, or a combination of at least two thereof.

7. The preparation method according to claim 3, characterized in that: The sintering in step (2) includes: a primary sintering and a secondary sintering performed sequentially, wherein the primary sintering temperature is 400-700°C and the time is 3-6 hours, and the secondary sintering temperature is 800-1100°C and the time is 10-30 hours.

8. The preparation method according to claim 3, characterized in that: The molten salt in step (3) includes one or more of lithium chloride, lithium nitrate, and lithium hydroxide; the molar ratio of lithium ions in the molten salt to sodium ions in the single crystal precursor P is greater than 3.

9. The preparation method according to claim 3, characterized in that: The sintering temperature in step (3) is 330°C-600°C, and the sintering time is 1-20h.

10. A lithium-ion battery, comprising the preferentially oriented single-crystalline lithium-rich manganese-based positive electrode material according to claim 1 or 2 or the preferentially oriented single-crystalline lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 3 to 9.

Citation Information

Patent Citations

  • Preparation method of layered lithium-rich manganese base oxide of positive material of lithium ion battery

    CN102683645A

  • Spherical or quasi-spherical lithium ion battery positive electrode material and lithium ion battery

    CN107359334A

  • Positive electrode material with high peak-to-intensity ratio as well as preparation method and application thereof

    CN114388777A

  • Lithium-rich manganese-based positive electrode material, precursor and preparation method thereof, lithium ion battery and electric equipment

    CN117747806A

  • Preparation method of layered oxide positive electrode material of sodium-ion battery

    CN118684282A

Cited By

  • Lithium-rich manganese-based positive electrode material and preparation method thereof, positive electrode plate, lithium secondary battery and electric equipment

    CN120565661A

  • Positive electrode material and preparation method thereof, positive plate and battery

    CN121035196A

  • O2 type lithium cobalt oxide precursor, preparation method and O2 type lithium cobalt oxide

    CN121202201A

  • Method for preparing lithium-rich manganese-based positive electrode material based on low-temperature sintering of composite lithium molten salt

    CN122494539A